2019
DOI: 10.1073/pnas.1818812116
|View full text |Cite
|
Sign up to set email alerts
|

Mutual interplay between IL-17–producing γδT cells and microbiota orchestrates oral mucosal homeostasis

Abstract: γδT cells are a major component of epithelial tissues and play a role in tissue homeostasis and host defense. γδT cells also reside in the gingiva, an oral tissue covered with specialized epithelium that continuously monitors the challenging dental biofilm. Whereas most research on intraepithelial γδT cells focuses on the skin and intestine epithelia, our knowledge on these cells in the gingiva is still incomplete. In this study, we demonstrate that even though the gingiva develops after birth, the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(151 citation statements)
references
References 49 publications
(73 reference statements)
11
138
0
1
Order By: Relevance
“…Recently, the local microbiome has emerged to play an important role in the homeostasis of Vγ6 + T cells . To control for the possibility that a unique microbiome in our animal facility affects Vγ6 + T‐cell homeostasis in the ageing cohort, we analysed pLNs from young and old mice housed in a different animal facility and obtained identical results (Appendix Fig S2A–F).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, the local microbiome has emerged to play an important role in the homeostasis of Vγ6 + T cells . To control for the possibility that a unique microbiome in our animal facility affects Vγ6 + T‐cell homeostasis in the ageing cohort, we analysed pLNs from young and old mice housed in a different animal facility and obtained identical results (Appendix Fig S2A–F).…”
Section: Resultsmentioning
confidence: 97%
“…IL-17 has been implicated in the development of chronic inflammation and autoimmunity. Preclinical infection models show that it is also essential for host defense against bacterial and fungal pathogens and in maintaining homeostasis, particularly at mucoepithelial surfaces (55,84). The dual roles of IL-17 appear to be conserved in humans, as heightened levels of expression have been linked to the development of Crohn's disease and psoriasis, whereas patients genetically deficient in IL17RA or expressing a dominant-negative form of IL17F are susceptible to mucocutaneous candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gingival γδT cells of adult mice are mainly composed of Vγ6+ (~60%) and Vγ1+ (~20%), while other subsets Vγ4+ (~10%), Vγ5+ (~5%) and Vγ7+ (~2%) are less enriched in this area [113]. They reside in the basal layer of the oral epithelium and in the junctional epithelium close to the dental biofilm, where they can reach the suprabasal layers [114]. It was demonstrated that during C. albicans infection in HIV patients the number of Vδ1 T cells was significantly higher when compared to HIV-patients with no infection.…”
Section: γδ T Cellsmentioning
confidence: 99%
“…They play an important role in OPC in mice, although TCR-δ−/− mice are mainly resistant to oral candidiasis [31]. γδ T cells can produce high amounts of IL-17 on a per-cell basis [119,120], and thus are potentially an important source of oral IL-17, which plays a crucial role in OPC [30,114]. Interestingly, the development of uterine γδ T cells in mice was independent from microflora, while Vγ6+ γδT cells in the gingiva were shown to be dependent [114,121].…”
Section: γδ T Cellsmentioning
confidence: 99%